Large-area bow-tie nanoantenna array for high-power high-order harmonic generation by field enhancement of surface plasmon resonance - Kim, Yong Soo; Jeong, Yeongkon; An, Young Jun; Jeong, Young Woo; Lee, Ju Han; Jhon, Young Min (Tsinghua Univ Press, 2025)
A bow-tie nanoantenna (BNA) array is one of the nanostructures most suitable for maximizing the field enhancement effect by surface plasmon resonance (SPR). Among several applications, the BNA array can enhance the intensity of pump lasers, especially in high-order harmonic generation (HHG). In this study, the focused ion beam (FIB)- scanning electron microscopy AutoScript 4 toolkit was used to automate the entire process of FIB milling and reduce the time required, spending less than 3 h fabricating a large area of 50 mu m x 50 mu m, and at the same time improving the quality of the BNA array through internal object control. In addition, diamond, which has a thermal conductivity more than 90 times higher than sapphire, was used as a substrate for the BNA array. For the first time in the world, the BNA was not damaged even when exposed to a laser intensity of 1012 W/cm2 for a long time. Surface-enhanced Raman scattering (SERS) measurements were performed by combining 4-aminothiophenol (4-ATP) as a probe molecule in fabricated large-area BNA arrays, confirming the large electric field enhancement in the gap of BNA, and the calculated enhancement factor (EF) was 8.83 x 109. In addition, the electric field simulation and heat transfer simulation using the finite element method (FEM) showed a 250-fold increase in the electric field based on the input unit electric field (1 V/m), a 9 times faster heat diffusion rate for the diamond substrate than the sapphire substrate based on the fall time, and 67.5 times faster the heat diffusion rate for the diamond substrate than the sapphire substrate based on the stabilization time. Therefore, both the experimental and simulation results showed that the fabricated large-area BNA array can be applied to high-power HHG.